Carpe diem - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Liaden Universe, 2020)
"On the run from interplanetary assassins, covert operative Val Con yos'Phelium and former mercenary sergeant Miri Robertson have wound up stranded on a distant planet with no rescue in sight. Until they figure out a way back to Liad, these two lost souls must find a way to trust each another-and let their love heal the dark wounds of their past. . . . Back on Liad, Shan yos'Galan, Val Con's cousin and foster brother, and his life-partner, Priscilla Mendoza, have initiated their own search for the missing member of Clan Korval. But what they don't know is that those who seek to destroy Val Con and Miri are just as determined to bring down Clan Korval. All the deadly enemy needs is someone to unwittingly lead them to their target. . . "--